2020
DOI: 10.1021/acsaem.0c02495
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport Properties of Lithium Superoxide in Li–O2Batteries

Abstract: The theoretical energy density of lithium–oxygen (Li–O2) batteries is extremely high, although there are many challenges that must be overcome to achieve high energy density in a manufactured cell. For example, little is known about the properties of one of the key intermediates, lithium superoxide (LiO2), which until recently had not been stabilized in bulk form. In this work, lithium superoxide was deposited onto iridium–reduced graphene oxide (Ir–rGO) cathodes in a Li–O2 system under a flow of O2. Lithium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…In the core-shell structure of 1, there are two components determining electron and ion conduction throughout the material: the LiO2 core and a Li[p-C6H4O2] shell. With regard to the core, recent experimental (72) and first-principles studies (73)(74)(75) have indicated that LiO2 possesses remarkable ionic and electronic conductivities, greatly exceeding that of other alkali superoxides and peroxides (75), presumably crucial properties necessary to form the structure shown in Fig. 10.…”
Section: Resultsmentioning
confidence: 99%
“…In the core-shell structure of 1, there are two components determining electron and ion conduction throughout the material: the LiO2 core and a Li[p-C6H4O2] shell. With regard to the core, recent experimental (72) and first-principles studies (73)(74)(75) have indicated that LiO2 possesses remarkable ionic and electronic conductivities, greatly exceeding that of other alkali superoxides and peroxides (75), presumably crucial properties necessary to form the structure shown in Fig. 10.…”
Section: Resultsmentioning
confidence: 99%
“…Then, an oxidative linear potential scan was applied to the discharged LOBs, and the evolved gaseous species were monitored with DEMS. It can be seen from panels a and b of Figure 1 that essentially no 16,18 O 2 is evolved for the two LOBs during the oxidative scan, which means that the O−O bond does not break during ORR and OER.…”
Section: Introductionmentioning
confidence: 98%
“…Toward unlocking the energy capabilities of LOBs, a wide spectrum of advanced characterization techniques has been employed to shed light on the mechanisms underpinning the operation of LOBs. For instance, differential electrochemical mass spectroscopy (DEMS) that can simultaneously measure the quantity of the gaseous species (e.g., O 2 and CO 2 ) and charge involved in the operation of LOBs has been used to study the reversibility of LOBs; surface-enhanced Raman spectroscopy (SERS) that can spectroscopically identify the reaction products (e.g., Li 2 O 2 and Li 2 CO 3 ) and intermediates (e.g., O 2 – and LiO 2 ) has been employed to formulate the elementary steps of Li–O 2 electrochemistry; electrochemical impedance spectroscopy that can obtain the electrical properties (e.g., resistance and capacitance) of the electrode|electrolyte interface has been used to follow the variation of charge transfer resistance and capacitance of the cathode|electrolyte interface during the operation of LOBs. Interested readers are encouraged to find more details of the advanced characterization techniques in refs . Among these wide range of the characterization techniques, isotope labeling is a unique and powerful research tool in the mechanistic studies of LOBs; specifically, it is good at tackling two fundamental issues in LOBs: (1) what are the reaction pathways and the associated intermediates and (2) where do these reactions take place?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synthesis approach that has been successful toward addressing this challenge is reverse microemulsion, which has been shown to lead to control over the nanostructure of complex oxide electrocatalysts (i.e., La 2 NiO 4 with a Ruddlesden–Popper (R-P) crystal structure) with well-defined oxide surface termination . Such electrocatalysts have been reported to possess selective catalytic properties toward the growth of non-traditional, electronically conductive Li-deficient discharge products (Li x O 2 ; 1 ≤ x < 2) in Li–O 2 cathodes with electrolytes containing low DN (<20) solvents. ,, Figure a clearly shows that the electrocatalyst nanostructure, and consequently the underlying (001)-NiO surface facets of La 2 NiO 4 nanorods, played a pivotal role in controlling the discharge product selectivity and the overall cell performance . Li–O 2 batteries containing (001)-NiO-terminated La 2 NiO 4 nanorod electrocatalysts exhibited a ∼0.7 V reduction in charge overpotentials, as compared to cathodes composed of only carbon or irregularly shaped La 2 NiO 4 nanostructures.…”
mentioning
confidence: 99%